Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Nguyễn Minh Hoàng

tính: \(\frac{6^6+6^3.3^3+3^6}{-73}\)

Thanh Tùng DZ
17 tháng 12 2017 lúc 21:08

\(\frac{6^6+6^3.3^3+3^6}{-73}\)

\(=\frac{3^6.\left(2^6+2^3+1\right)}{-73}\)

\(=\frac{3^6.73}{-73}\)

\(=3^6.\left(-1\right)=-729\)


Các câu hỏi tương tự
nguyen thu trang
Xem chi tiết
Lê Đức Khanh
Xem chi tiết
tuyen tuyen
Xem chi tiết
Long Phùng Linh Giang
Xem chi tiết
Nguyen Thanh Hai
Xem chi tiết
Mai Phương Nguyễn
Xem chi tiết
Trangg Vân
Xem chi tiết
๖ۣۜTina
Xem chi tiết
Lân Dũng
Xem chi tiết